THE FOLKLORE CREATION CIULEANDRA IN THE JAZZ INTERPRETATIVE VERSION OF THE COMPOSER A. ȘTEFĂNET - PINTILIE-ROMANENCO, CRISTINA (Notograf Prim, 2021)
In the center of the author’s attention is the composition „Ciuleandra” from M.Tănase’s repertoire in the performing vision of A. Ștefaneț, leader of „Trigon”, ethno jazz group, which represents a unique example in the contemporary jazz practice of the Republic of Moldova. This piece demonstrates a fusion of instrumental jazz and popular theatre traditions. In „Ciuleandra” the influence of the popular theater is manifested throughout the work based on a recitative dialogue between the two out of the six female soloists. A. Ștefănet transforms the original musical material in an innovative way changing the melodic and metro-rhythmic background of the piece. The instrumental ensemble structure is less traditional: here the string quartet of classical origin is harmoniously combined with the rhythm section of jazz origin (percussion and piano) slightly altered by the inclusion of the instrument from the folk orchestra (accordion) and soprano saxophone as soloist.